Medical Center for Remote Monitoring of COVID-19 patients: organization experience and efficiency assessment - V. A. Boykov; S. A. Baranovskaya; I. A. Deev; E. V. Taranukha; I. P. Shibalkov; M. A. Babeshina (Бюллетень сибирской медицины)
Aim. To summarize the experience of organizing and evaluating the efficiency of the Medical Center for Remote Monitoring of patients with COVID-19 and community-acquired pneumonia in Tomsk.Materials and methods. The project of the Medical Center for Remote Monitoring was developed on the basis of data from theoretical and empirical analyses of the current state of the healthcare system in the Tomsk region and the epidemiological situation with regard to COVID-19. The Center efficiency was assessed based on the analysis of quantitative and time indicators of the load on the emergency medical service and outpatient service. Statistical processing of the results was carried out using the Statistica 12.0 software package.Results. On October 20, 2020, in Tomsk, on the premises of the “Emergency medical unit”, a Medical Center for Remote Monitoring was established. It was aimed at providing remote consultations for patients with COVID-19 and community-acquired pneumonia. According to its algorithm, operators  of the Center assessed a patient’s condition on a point scale using standardized speech modules to make a decision on the tactics of their support. During the second wave of COVID-19, when the Center operated, a statistically significant decrease in the load on the ambulance service (average number of calls per day, average waiting time for all calls and  coronavirusrelated calls) as well as on the outpatient service (average  number of house calls per day, including calls for acute respiratory diseases) was registered.Conclusion. The work of the Medical Center for Remote Monitoring based on the described model is associated with a decrease in the load on the healthcare system in an unfavorable epidemiological situation due to high COVID-19 incidence. This experience can be spread to other regions of  Russia and adapted for other categories of citizens.